2020
DOI: 10.1371/journal.pone.0230784
|View full text |Cite
|
Sign up to set email alerts
|

The role of small intestinal bacterial overgrowth and false positive diagnosis of lactose intolerance in southwest Hungary—A retrospective observational study

Abstract: Background Lactose intolerance is a frequent gastrointestinal disease affecting 47% of the Eastern European population. Small intestinal bacterial overgrowth (SIBO) leads to carbohydrate malabsorption and therefore to false results during lactose breath and tolerance tests. Objectives We aimed to assess the prevalence of lactose maldigestion and intolerance in Hungary and to investigate the role of combined diagnostic method and testing for SIBO in reducing false results. Methods We retrospectively analyzed da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Diseases that cause secondary lactose intolerance, such as celiac disease, can also lead to disagreement between test results. One study carried out with Italian adults using the hydrogen breath test showed that the frequency of celiac disease was significantly higher in patients with lactose malabsorption than in those without malabsorption (30) ; celiac disease occurs due to a loss of intestinal mucosa integrity and secondary lactase deficiency resulting in lactose malabsorption (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Diseases that cause secondary lactose intolerance, such as celiac disease, can also lead to disagreement between test results. One study carried out with Italian adults using the hydrogen breath test showed that the frequency of celiac disease was significantly higher in patients with lactose malabsorption than in those without malabsorption (30) ; celiac disease occurs due to a loss of intestinal mucosa integrity and secondary lactase deficiency resulting in lactose malabsorption (31) .…”
Section: Discussionmentioning
confidence: 99%
“…In the same sense, Varjú et al (2020) concluded that most of the cholesterol removed by Lactobacillus acidophilus L1 and ATCC 43121 strains was by incorporation, considering the possibility of cholesterol being incorporated into the bacterial cell membrane. Similar results were observed by Jeong et al (2013), who reported that probiotic bacteria are capable of producing enzymes that disjugate bile acids, the so-called bile salt hydrolases, these when disjugated are less reabsorbed when compared to conjugated bile acids, which results in increased excretion of these acids in the feces.…”
Section: Laboratory Analysis Of the Lipid Profilementioning
confidence: 96%
“…Fukushima et al, (2005) attributed the reduction in serum cholesterol concentration in rats fed a hypercholesterolemic diet that received the probiotic microorganism Amylomyce rouxii, to an increase in AGCC production and to an increase in the expression of LDL-c receptors in the liver. Varjú et al (2020) conducted a study with healthy and lactose-intolerant men, and concluded that chronic consumption of probiotic yogurt increased the concentrations of propionate and butyrate, which may promote long-term improvement in lipid and glucose metabolism.…”
Section: Laboratory Analysis Of the Lipid Profilementioning
confidence: 99%
“…A false-negative test may appear due to non-H 2 producing microbiota. Methanogenic bacteria in some people transform hydrogen into methane, giving a low percentage of positive tests (53,54).…”
Section: Clinical Diagnosis Of Lactose Maldigestionmentioning
confidence: 99%